Changes in properties of reclaimed-mine soil, plant growth, and metal accumulation in plants with application of coal fly ash and empty fruit bunches of oil palm - Saidy, Akhmad Rizalli; Priatmadi, Bambang Joko; Septiana, Meldia; Ratna, Ratna; Fachruzi, Ismet; Ifansyah, Hairil; Hayati, Afiah; Mahbub, Muhammad; Haris, Abdul (Brawijaya University, 2024)
Reclaimed-mining soil (RMS) is characterized by low fertility, acidic pH, and high heavy metal contents. As a result, adding amendments becomes essential to support plant growth. Therefore, this research measured alterations in the characteristics of RMS, plant growth, and metal accumulation in plants with the co-application of coal fly ash (CFA) and empty fruit bunches of oil palm (EFBOP). In the first experiment, various levels of CFA (0, 75, and 150 Mg ha-1) and EFBOP (0, 25, and 50 Mg ha-1) were added to the RMS and then incubated at 70% water holding capacity for 45 days to determine their effect on changes in soil properties. In the second experiment, four treatments: control, CFA, EFBOP, and CFA+EFBOP were tested in the greenhouse to quantify their effects on the growth and metal accumulation of plants. Results of the study showed that the co-application of CFA and EFBOP significantly affected bulk density, pH, mineral nitrogen (NH4+ and NO3-), available phosphorus, and exchangeable Ca and Mg in RMS. CFA application increased exchangeable Al by 82-160%, while EFBOP resulted in a decrease of 24-119%. CEC decreased with CFA application and increased with the use of EFBOP. Plant growth increased with the co-application of CFA and EFBOP. The addition of CFA to soils results in increasing metal contents in plant tissue; however, the presence of EFBOP reduced the concentrations of metal in plant tissue. These results highlight the potential of CFA and EFBOP, which are industrial and agricultural wastes, as valuable soil amendments.